(NwULKAN (B/s - (NzAWARICKAQ(B, (Ne(B.(Np(B.s; (NzAWARICKIJ(B, (Na(B.(Nn(B.s ((NmOSKWAs (NlENINGRAD (B:s (NgOS(B.(NIZD(B. (NTEHNIKO(B-(NTEOR(B. (NLIT(B.,s, 1949)
(NzAK(B.: (NS(B. 42-44s
Keywords: (NwULKANIZM(B. (NwULKANY I WULKANI^ESKIE SISTEMY(B. (NiZWERVENIQ WULKANOW I QWLENIQ(B, (NSWQZANNYE S IZWERVENIQMIs